Day 3 Wed, September 28, 2016 2016
DOI: 10.2118/181404-ms
|View full text |Cite
|
Sign up to set email alerts
|

The PetroChallenge – An Innovative E&P Learning Experience Using an Interactive Learning Simulation

Abstract: For decades, the university education has provided a base foundation and prepared students to join the workforce. Despite the technical foundation, students lack practical exposure. To bridge the practical knowledge gap, the industry has launched various short duration interns/externs programs. Even then these programs are not broad enough to provide a holistic understanding of the Oil and Gas Industry. Therefore, in 2015 to address this practical application NExT, a Schlumberger company, launched an interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Additionally we have found that group-challenge problems and business simulations help to connect problem solution with engineering skills and analysis. Examples are provided in two separate papers. , This is an area we are exploring for future classroom use.…”
Section: Coupled Learning and Innovation Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally we have found that group-challenge problems and business simulations help to connect problem solution with engineering skills and analysis. Examples are provided in two separate papers. , This is an area we are exploring for future classroom use.…”
Section: Coupled Learning and Innovation Processesmentioning
confidence: 99%
“…Examples are provided in two separate papers. 34,35 This is an area we are exploring for future classroom use.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%